DNA Microarray Analysis of Labial Salivary Glands in IgG4‐Related Disease: Comparison With Sjögren's Syndrome. Issue 10 (October 2014) - Tsuboi, Hiroto; Nakai, Yuji; Iizuka, Mana; Asashima, Hiromitsu; Hagiya, Chihiro; Tsuzuki, Sayaka; Hirota, Tomoya; Miki, Haruka; Hagiwara, Shinya; Kondo, Yuya; Tanaka, Akihiko; Moriyama, Masafumi; et al.
<x xml:space="preserve">Abstract</x> Objective To compare gene expression in labial salivary glands (LSGs) from patients with IgG4‐related disease with that in LSGs from patients with Sjögren's syndrome (SS). Methods Gene expression was analyzed by DNA microarray in LSG samples from 5 patients with IgG4‐related disease, 5 SS patients, and 3 healthy controls. Genes differentially expressed in IgG4‐related disease and SS were identified, and gene annotation enrichment analysis of these differentially expressed genes was performed using Gene Ontology (GO) annotation. Validation of the results was performed by quantitative polymerase chain reaction (PCR) using LSG samples from 9 patients with IgG4‐related disease, 10 SS patients, and 4 controls. Results Gene expression patterns in patients with IgG4‐related disease, SS patients, and healthy controls were quite different from each other in hierarchical clustering as well as in principal components analysis. In IgG4‐related disease compared with SS, a total of 1, 771 probe sets (corresponding to 1, 321 genes) were identified as up‐regulated, and 1, 785 probe sets (corresponding to 1, 320 genes) were identified as down‐regulated (false discovery rate of <5%). GO term analysis indicated that the up‐regulated set of differentially expressed genes in IgG4‐related disease encoded proteins that function in cell proliferation, extracellular matrix organization, and organ development. PCR validated significantly higher expression of lactotransferrin in patients with IgG4‐related disease than in SS patients (P < 0.05) and significantly higher expression of CCL18 in patients with IgG4‐related disease than in SS patients and controls (P < 0.05). Conclusion The results clearly showed that the gene expression pattern in LSGs from patients with IgG4‐related disease is different from that in LSGs from SS patients.